IMPLEMENTATIONNON-COMMUNICABLE DISEASE MANAGEMENT POLICY IN PALU CITY - Made Lusiana, Ni; Rivai, Abdul; Nuraisyah, Nuraisyah (Penerbit Lafadz Jaya, 2023)
This research aims to analyze the implementation of non-communicable disease (PTM) prevention policies at the Sangurara Community Health Center, Palu City. Descriptive qualitative methods are used to explain the implementation of integrated PTM services with a focus on communication, resources, disposition and bureaucratic structure. The research location at the Sangurara Community Health Center was chosen because it will become a training center related to PTM after 2022. Data was obtained through in-depth interviews, field observations and documentation. The research results show that communication still faces obstacles in disseminating policies to the public. Human resources and physical facilities at the Sangurara Community Health Center are considered inadequate, while the disposition of the management and health workers is quite good. The bureaucratic structure shows the existence of SOPs and coordination, although attention needs to be paid to internal communication between units. In conclusion, the implementation of the PTM policy at the Sangurara Community Health Center is going well with obstacles, especially communication and resources. This research provides insight into increasing the effectiveness of PTM policy implementation.